Destination Competitiveness Aspect for Cultural Tourism Area in Museum of Fine Arts and Ceramics in Jakarta, Indonesia - Pratiwi, A (KnE Social Sciences, 2018)
The purpose of this article is to know more about the Museum of Fine Arts and Ceramics in the old town city of Jakarta because the museum is a part of a cultural tourism destination. The museum has as much potential as the other museums and can become a competition destination for other museums. The research was conducted in April 2017 with qualitative approaches—interview and discussion with two respondents that comprised representation from the museum. In addition, some of the data were also produced from secondary sources such as official website and books. The Museum of Fine Arts and Ceramics has the ability to develop aspects of internal factors, attractions and accommodation facilities. The quality of the museum’s development is to focus on destination management & competitiveness and also the marketing formulation strategy as a result of organized planning processes. With those conditions, they have an advantage as a basic foundation of their tourism development. This article illustrates a detailed analysis of the destination’s competitiveness with its development strategy, and more distinctive understanding of what supporting facilities are provided by the museum—a destination’s competitive position. Keywords: cultural, destination competitiveness, destination development strategy, museum of fine arts and ceramics, potential development